Spirituality, Personality, and Emotional Distress During COVID-19 Pandemic in Croatia - Margetić, Branimir (Journal of religion and health, 2022)
This study examined the association between spiritual quality of life (QoL), spiritual coping, emotional distress, and personality during the COVID-19 pandemic lockdown in a convenience sample of Croatian adults (n = 2,860, 80.6% women). Participants completed an online questionnaire that collected information on sociodemographic characteristics, distress (the Depression, Anxiety, and Stress Scale 21), spiritual coping and spiritual QoL (the WHO Quality of Life-Spirituality, Religiousness, and Personal Beliefs), and personality (the International Personality Item Pool). The hierarchical regression analysis demonstrated that personality traits, especially emotional stability, were the most significant predictors of mental health outcomes. Spiritual coping styles were a predictor of worse, while spiritual QoL of better psychological outcomes. Results demonstrate the complex relations between different aspects of spirituality/religiosity with personality and emotional outcomes and suggest that distress motivates the engagement of spiritual coping in times of disaster.